The Disruptive bEhavior manageMEnt ANd prevention in hospitalized patients using a behaviORal intervention team (DEMEANOR) study protocol: a pragmatic, cluster, crossover trial - Jay Morrison; Michele Hasselblad; Ruth Kleinpell; Reagan Buie; Deborah Ariosto; Erin Hardiman; Stephen W. Osborn; Christopher J. Lindsell; for the Vanderbilt Learning Healthcare System Investigators, Vanderbilt University (Trials, 2020)
Abstract Background Disruptive behavior in hospitalized patients has become a priority area of safety concern for clinical staff, and also has consequences for patient management and hospital course. Proactive screening and intervention of patients with behavioral comorbidities has been reported to reduce disruptive behavior in some settings, but it has not been studied in a rigorous way. Methods The Disruptive bEhavior manageMEnt ANd prevention in hospitalized patients using a behaviORal intervention team (DEMEANOR) study is a pragmatic, cluster, crossover trial that is being conducted. Each month, the behavioral intervention team, comprising a psychiatric-mental health advanced practice nurse and a clinical social worker, with psychiatrist consultation as needed, rotates between an adult medicine unit and a mixed cardiac unit at Vanderbilt University Medical Center in Nashville, TN, USA. The team proactively screens patients upon admission, utilizing a protocol which includes a comprehensive chart review and, if indicated, a brief interview, seeking to identify those patients who possess risk factors indicative of either a potential psychological barrier to their own clinical progress or a potential risk for exhibiting disruptive, aggressive, or self-injurious behavior during their hospitalization. Once identified, the team provides interventions aimed at mitigating these risks, educates and supports the patient care teams (nurses, physicians, and others), and assists non-psychiatric staff in the management of patients who require behavioral healthcare. Patients who are both admitted to and discharged from either unit are included in the study. Anticipated enrollment is approximately 1790 patients. The two primary outcomes are (1) a composite of objective measures related to the patients’ disruptive, threatening, or acting out behaviors, and (2) staff self-reported comfort with and confidence in their ability to manage patients exhibiting disruptive, threatening, or acting out behavior. Secondary outcomes include patient length of stay, patient attendant (sitter) use, and the unit nursing staff retention. Discussion This ongoing trial will provide evidence on the real-world effectiveness of a proactive behavioral intervention to prevent disruptive, threatening, or acting out events in adult hospitalized patients. Trial registration ClinicalTrials.gov: NCT03777241 . Registered on 14 December 2018.